Analysis of Business Development Strategy and Product Variations On Medium-sized Enterprises Small Micro Corn Banyubang - Ratna Handayati; Sabilar Rosyad; Eka Nur Fauziyah (Publisher Cv. Inara, 2020)
AbstrakThis research aims to determine the general overview in the production cooperativeAgrobisnis Mrs. Mandiri Desa Banyubang, Solokuro subdistrict, and to know itsbusiness development strategy. The method of data analysis used is 1) qualitativedescriptive analysis to know the general overview of Corn Snack business strategy,2) SWOT analysis to identify internal and external factors that become strengths,weaknesses, opportunities and A threat in the business development of corn snacks.Based on the results of the study in the discussion can be concluded that the farmergroup of Women Mandiri is one of the farmer group in Banyubang village, Solokurosubdistrict, which was formed in 2016 and did a snack business made The base ofcorn, which all members consist of Mother women – housewives in Banyubangvillage. Based on the results of the research from SWOT analysis obtained thecoordinate point (1.47:2.03) which is the coordinate of the 1 (aggressive) quadrant,meaning that the corn snack business on the Agrobisnis Ibu Mandiri ProductionCooperative has the strength and opportunity Well, so that the self-reliant motherfarmer Group can harness the strengths and opportunities that exist to expand thenext corn snack business.